Teachers’ and School Professionals’ Knowledge and Attitudes Towards Epilepsy in Greece: Misconceptions and Management Options for Affected Students—A Survey Study - Stergiani Pitta; Angelos Papadopoulos; Eirini Tsiamaki; Angeliki Tsapanou; Nikolaos Trimmis; Emilia Michou; Eleni Jelastopulu; Panagiotis Plotas (Education Sciences)
Epilepsy remains one of the most prevalent neurological disorders affecting school-aged children, often accompanied by social stigma and misconceptions that can hinder their academic and social development. Background and Objectives: Given the critical role of teachers and school professionals in the daily lives of children with epilepsy, this study aimed to assess the knowledge, attitudes, and behaviors of primary school teachers and professionals in Greece regarding epilepsy. The findings are intended to identify gaps and inform the development of targeted educational interventions that support managing epilepsy effectively. Materials and Methods: A cross-sectional survey was conducted with 546 primary education teachers in Western Greece using a questionnaire adapted from a validated Italian study. This survey collected demographic information and assessed knowledge, attitudes, and school-related practices concerning epilepsy. Data were analyzed with IBM SPSS, employing descriptive and inferential statistics to explore relationships between demographics and responses. Results: Although most participants were generally aware of epilepsy, considerable gaps persisted in knowledge about prevalence, causes, and proper seizure management. Notably, over half of the participants were unsure how to manage an epileptic episode, and misconceptions about the effects of antiepileptic drugs on learning and behavior were prevalent. Participants with special education experience displayed more accurate knowledge and greater confidence in handling epilepsy-related situations. Conclusions: This study underscores the need for enhanced epilepsy education among primary school teachers and school professionals in Greece to address knowledge gaps, reduce stigma, and better support the educational and social needs of students with epilepsy. Coordinated efforts with educational authorities and health organizations are recommended to implement specialized teacher training programs.